Improving Product Quality and Marketing Strategies In The Rengkek Latukan (Korela) Community - Khoirotun Ni'mah; Ida Latifatul Umroh; Hubabah; Zuli Kasmawanto (Shof Journal of Social Impact, 2024)
Abstract: A rengkek trader is a street vendor who sells his merchandise by going around to villages using a rengkek placed on the back of his motorcycle. The Latukan rengkek community is a traveling merchant that sells various types of food consisting of various fried foods, wet cakes, side dishes and pauk. The food sold by the rengkek community is produced by a group of mothers in Latukan village. This community service aims to help the Latukan rengkek community in improving the quality of the products sold and assisting in the field of marketing strategy so that the goods produced have many enthusiasts so that producers do not lose much. This community service activity is carried out using Assed Based Community Development (ABCD). With the ABCD approach, it can prioritize the use of local village assets or potential. The ABCD method consists of five steps, namely discovery, dream, design, define, and destiny. With this community service program, it is hoped that it can contribute thoughts to the Latukan rengkek community in order to improve the quality of products starting from packaging, the taste of processed food so that it is delicious and in great demand by consumers and food does not spoil quickly. Apart from product quality, marketing strategies are also very important for Latukan rengkek traders.